Determination of the Communication Skills of University Students by Sociodemographic Features - AKYURT, NURAN (E D P SCIENCES, 2018)
As a social being, human life continues in communities with other people. Human being is the only entity that communicates with highly complex learned behaviors that include best use of gestures and mimics, advanced reflex and instinct language as well as language. In our study, we wanted to determine the communication skills of university students with their socio-demographic characteristics. Two separate forms were used in the study. The evaluation of the obtained data was done by SPSS (Version 16.0) Statistical Package Program. The target population of the study is composed of students studying at Marmara University. In the direction of the data obtained within the scope of the research it was observed that the communication skills of the students studying in the departments providing health education are higher. University students are encouraged to develop listening skills and create an environment in which they can express themselves better.